Genetic Diversity of Mycobacterium tuberculosis Isolates From an Amerindian Population in Chiapas, México - Molina-Torres, Carmen A.; Quinn, Frederick D.; Castro-Garza, Jorge; Gómez-Velasco, Anaximandro; Ocampo-Candiani, Jorge; Bencomo-Alerm, Alied; Sánchez-Pérez, Héctor Javier; Muñoz-Jiménez, Sergio; Rendón, Adrián; Ansari, Afzal; Sharma, Mukul; Singh, Pushpendra; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
This is the first report of the genetic diversity of the Mycobacterium tuberculosis complex isolates found in a Mexican-Amerindian setting. In this study, we analyzed isolates collected from the Highlands region of Chiapas, Mexico, by using spoligotyping and whole genome sequencing analyses. Seventy-three M. tuberculosis isolates were analyzed initially by spoligotyping; no new spoligotypes were identified. Nineteen percent of the isolates were identified as SIT53 (T1) (n=14), followed by SIT42 (14%, n=10, LAM9) and SIT119 (11%; n=8, X1). SIT53, SIT42 and orphan isolates (16.4%, n=12) constituted about 50% of the isolates studied and were subjected to whole genome sequencing (WGS) analysis. Most SIT53 (10/12) isolates belonged to the Euro-American sub-lineage 4.8. Most SIT42 isolates (4/7), as well as most orphan isolates (5/8) belonged to the lineage 4.3.3 LAM group. By comparing the single nucleotide polymorphism (SNP) patterns of the SIT53 isolates, we found one clone (<7 SNPs) and four clustered isolates (<15 SNPs). In isolates from the SIT42 and orphan groups we did not find any clones or clusters. This work demonstrates the success of sublineage 4.8 to predominate in Mexico and confirms the dominion of sublineage 4.3.3 in Central and South America.